1977
DOI: 10.1152/ajprenal.1977.232.1.f16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute unilateral renal denervation on tubular sodium reabsorption in the dog

Abstract: The effects of acute denervation of the kidney on renal tubular sodium and water excretion were studied in anesthetized, hypophysectomized, and cortisone-treated mongrel dogs during stable water diuresis produced by the infusion of 2.5% dextrose. In all experiments, denervation natriuresis, and diuresis were observed without significant change in glomerular filtration rate (GRF) and renal plasma flow (RPF). Fractional sodium delivery to the distal nephron (CNa + CH2O/100 ml GFR) and fractional free water clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Stimulation of renal sympathetic nerves or renal arterial infusion of NE enhance renal tubular reabsorp tion of sodium independent of changes in renal hemody namics [41][42], Renal denervation in the anesthetized rat [43] and dogs [44][45] increased urine volume and urine sodium excretion while GFR and RBF remained unchanged and fractional and absolute sodium and water reabsorption decreased in the proximal tubule. Studies in conscious animals have shown that intact renal innervation is neces sary for normal renal adaptation to sodium restriction [46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of renal sympathetic nerves or renal arterial infusion of NE enhance renal tubular reabsorp tion of sodium independent of changes in renal hemody namics [41][42], Renal denervation in the anesthetized rat [43] and dogs [44][45] increased urine volume and urine sodium excretion while GFR and RBF remained unchanged and fractional and absolute sodium and water reabsorption decreased in the proximal tubule. Studies in conscious animals have shown that intact renal innervation is neces sary for normal renal adaptation to sodium restriction [46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the evidence provided by Nomora et al 37 shows that rsna primarily affects the proximal tubule sodium reabsorption, hence it seems plausible to exclude the effects of rsna on sodium reabsorption at other parts of the renal tubular system. The effect of rsna on fractional proximal sodium reabsorption (γ rsna ) has been modeled by curve fitting to the data provided in 8 and 35 [Eq.…”
Section: Proposed Modelmentioning
confidence: 97%